Can the arts enhance postgraduate GP training?. Issue 2 (3rd March 2020) - Forde, Emer; Scallan, Samantha; Jackson, Susie; Bowditch, Will; Wedderburn, Clare
ABSTRACT: The value of arts-based medical education is becoming increasingly well established in undergraduate curricula. However, little is known about its value, and acceptability, to qualified doctors undertaking postgraduate training. In this work we examined GP trainees' views on whether arts-based education was useful for their professional development and, if so, what they perceived its value to be. All first and second year GP trainees on the Dorset Vocational Training Scheme attended a one day course which showcased how the arts (film, poetry, painting, photography, theatre) could enhance their professional development as doctors. GP trainees rated the day as interesting, enjoyable and thought proving. The majority felt that the arts could contribute to making them more competent and humane doctors. Following this, we ran a mandatory six months arts based course for six GP trainees, and evaluated their feedback through qualitative analysis of a focus group discussion. Overall, GP trainees found the course enjoyable and valuable to their learning. It not only gave them a deeper appreciation of the patient's perspective, but also encouraged them to think about their own health and wellbeing.